The role of neutrophils and NETosis in lipopolysaccharide exacerbated asthmatic airway inflammation - Qian, Qian; Zhao, Qianye; Qian, Yongji; Deng, Huan; Feng, Xiaoming; Zhang, Jiamin; Huang, Xia; Du, Yi; Zhao, Deyu; Liu, Feng (Frontiers in Immunology, 2025)
BackgroundLipopolysaccharides (LPS) are associated with the exacerbation of asthma, accompanied by an increased recruitment of neutrophils to the airway. The role of these neutrophils warrants thorough investigation.MethodsIn this study, three genotypes of mice were utilized to establish an asthma model aggravated by LPS combined with ovalbumin (OVA). The bronchoalveolar lavage fluid (BALF) of mice was obtained to detect neutrophil-related inflammatory factors. Lung tissues were collected for staining, and neutrophils derived from bone marrow of mice were subjected to transcriptomic sequencing analysis.ResultsOur findings revealed that, compared to eosinophilic asthma, Exacerbated asthma triggered by LPS combined with OVA showed more severe airway inflammation. Neutrophil-related markers like IL6, IL8, and neutrophil extracellular traps (NETs) were significantly elevated in this model. Inhibiting neutrophils production significantly improved airway inflammation and lung function. Analysis of differentially expressed genes (DEGs) in bone marrow neutrophils highlighted enrichment in the NETs pathway. Suppressing NETs yielded similar results to decreasing neutrophils.ConclusionOur results indicate that NETs are involved in the pathogenesis of LPS exacerbated asthmatic airway inflammation, and targeting the NETosis function of neutrophils may represent an effective therapeutic approach.